Variations in the Response of Real Output to Aggregate Demand Shocks: A Cross-Industry Analysis - Kandil, Magda (The Review of Economics and Statistics, 1991)
Using industry data, this paper investigates the determinants of the response of real output to aggregate demand shocks across industries of the U.S. economy. The purpose of this investigation is to verify the empirical validity of two competing explanations for this response: a new classical explanation and a new Keynesian explanation. The author finds that the impact of aggregate demand shocks on industrial real output is negatively related to the mean inflation of industrial output price and positively related to the variability of the demand for this output. In addition, some industry-specific factors are important in differentiating the cyclical behavior of real output across industries. This evidence does not provide a clear support for any of the competing explanations considered in this paper. The evidence, however, sheds some light on important factors that differentiate the response of real output to aggregate demand shocks across industries of the economy. Copyright 1991 by MIT Press.